Antibiotics in IBD: Still a Role in the Biological Era?. Issue 8 (2nd May 2018) - Ledder, Oren; Turner, Dan
Abstract: Despite compelling evidence pointing to a critical role of gut microflora in inflammatory bowel disease (IBD) pathogenesis, the role of antibiotics in clinical practice remains limited, largely due to heterogeneous trials with often conflicting evidence. In this review, we revisit previous randomized controlled trials and high-quality uncontrolled studies in an effort to better elucidate the role of antibiotics in contemporary treatment algorithms. The most established role of antibiotics is in perianal Crohn's disease (CD), utilizing ciprofloxacin with or without metronidazole often as an adjunct to biological therapy. Evidence also points to a likely modest role of various antibiotic classes in mild to moderate luminal CD, including ciprofloxacin, metronidazole, azithromycin, and rifaximin. The benefit of metronidazole in preventing postoperative recurrence in CD is well reported; however, the long-term benefit of this intervention remains uncertain. The use of antibiotics in ulcerative colitis (UC) is even more controversial, but studies using broad-spectrum oral antibiotic cocktails have reported a possible role in acute severe colitis and chronic persistent UC. Similarly, the role of oral vancomycin and gentamicin in very early-onset IBD has interesting preliminary results. Adverse events of antibiotics, the resulting alterations in the microbiome with its associated unknown long-term sequela, and the emergence of antibiotic-resistant strains must be carefully balanced. Therefore, although antibiotics may be underused in the treatment of IBD, their integration into clinical practice must be approached judiciously and individually.